2020
DOI: 10.1021/acs.jmedchem.0c01049
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Innate Immune Response by Targeting Toll-like Receptors: A Perspective on Their Agonists and Antagonists

Abstract: Toll-like receptors (TLRs) are a class of proteins that recognize pathogen-associated molecular patterns (PAMPs) and damaged-associated molecular patterns (DAMPs), and they are involved in the regulation of innate immune system. These transmembrane receptors, localized at the cellular or endosomal membrane, trigger inflammatory processes through either myeloid differentiation primary response 88 (MyD88) or TIR-domain-containing adapter-inducing interferon-β (TRIF) signaling pathways. In the last decades, exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 317 publications
0
70
0
Order By: Relevance
“…Under the context of DNA virus infection, the innate immune system has to be able to detect DNA from pathogens in order to induce a strong antiviral innate immune response. 62 It is reported that DNA vaccination relies on DNA sensing to invoke a powerful innate immune response that, in turn, assists the adaptive response. 63 DNA can also act as a damage-associated molecular pattern (DAMP), accelerating inflammatory responses following its release from dying or damaged cells directly contributing to the pathogenesis of various diseases such as atherosclerosis 64 and deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Under the context of DNA virus infection, the innate immune system has to be able to detect DNA from pathogens in order to induce a strong antiviral innate immune response. 62 It is reported that DNA vaccination relies on DNA sensing to invoke a powerful innate immune response that, in turn, assists the adaptive response. 63 DNA can also act as a damage-associated molecular pattern (DAMP), accelerating inflammatory responses following its release from dying or damaged cells directly contributing to the pathogenesis of various diseases such as atherosclerosis 64 and deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are known to primarily stimulate the nonspecific immune responses (innate immunity), in which the mediators of immune system including cytokines, macrophages, neutrophils, acute-phase proteins and monocytes provide instant defense against pathogens ( 60 ). Pathogens express different factors known as pathogen-associated molecular patterns (PAMPs), which are recognized by the host to perceive the presence of pathogens.…”
Section: Treatment Of Viral Diseases Using Natural Immunomodulatorsmentioning
confidence: 99%
“…PAMPs are recognized by host sensors using PRRs triggering a sequence of immune reactions through the generation of type-1 IFNs, cytokines, and chemokines. PRR families include NOD-like receptors, Toll-like receptors (TLRs), RIG-I-like receptors and DNA receptors ( 60 ). TLR-3, -7,- 8, and -9 are extremely important in sensing viral infections as they transduce signals to the system, which then activates antiviral processes.…”
Section: Treatment Of Viral Diseases Using Natural Immunomodulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon TLR4 activation, two distinct adapter proteins are recruited to induce two parallel pathways and it is interesting to note that TLR4 is the only member of the TLR family that is able to activate both these pathways (Federico et al, 2020). For the first pathway, the TIRAP adapter binds to the TIR domain of the receptor and then recruits MyD88 that serves as one of the most important activator proteins connecting many signaling pathways in the cells.…”
Section: The Molecular Mechanisms Of the Tlr4 Pathwaymentioning
confidence: 99%